Hematite Nanoparticles-Modified Electrode Based Electrochemical Sensing Platform for Dopamine. (21st July 2014) - Zangeneh Kamali, Khosro; Alagarsamy, Pandikumar; Huang, Nay Ming; Ong, Boon Hoong; Lim, Hong Ngee
Abstract : Hematite ( α -Fe2 O3 ) nanoparticles were synthesized by the solid transformation of ferrous hydroxide and ferrihydrite in hydrothermal condition. The as-prepared α -Fe2 O3 nanoparticles were characterized by UV-vis, PL, XRD, Raman, TEM, AFM, FESEM, and EDX analysis. The experimental results indicated the formation of uniform hematite nanoparticles with an average size of 45 nm and perfect crystallinity. The electrochemical behavior of a GC/ α -Fe2 O3 electrode was studied using CV and EIS techniques with an electrochemical probe, [Fe(CN)6 ] 3−/4− redox couple. The electrocatalytic activity was investigated toward DA oxidation in a phosphate buffer solution (pH 6.8) by varying different experimental parameters. The chronoamperometric study showed a linear response in the range of 0–2 μ M with LoD of 1.6 μ M for DA. Square wave voltammetry showed a linear response in the range of 0–35 μ M with LoD of 236 nM for DA.